Pig Production in Gulu and Omoro Districts of Northern Uganda - Kasima, J. S.; Mugonola, B.; Ndyomugyenyi, E. K. (Stechnolock Vet Sci, 2021)
The pig of use inadequate by constrained is farmers smallholder of livelihoods the improve to production pig of potential suggested been have breeds improve to) AI (insemination artificial of use the like Technologies. technologies production such of use limited suggesting low remains, however, Uganda Northern in production Pig. production pig improve to feed of use and insemination artificial, technology) IMO (organism-Micro Indigenous (technologies Three. technologies districts Omoro and Gulu in farmers smallholder the to introduced were) feedstuffs available locally dominant from formula farmers among production pig of status the that necessitated it, however, implementation to Prior. Uganda northern of paper This. assessed be will technologies these introduce to initiative the of impact the which against established be out carried was survey sectional-cross A. Uganda northern in production pig of status the determining at aimed therefore ,males were% 6.59. implementation technology in participate to recruited farmers pig selected purposively 109 among primary attained had%), 2.42 (members 9-7 of size household with%), 78 (married%), 2.53 (years 64-36 between aged local keeping farmers% 4.67 with pigs 6.4 was size herd average The%). 1.54 (land of acres 5-1 had and%) 7.58 (education Income. species livestock main the as pigs keeping farmers% 89 with districts both in herds the dominated Piglets. pigs diseases and%) 6.82 (feeding expensive by constrained was Piggery. pigs keeping for reason primary the was generation used none but pigs their housed% 6.59, formula definite no with feedstuffs local on pigs fed farmers% 6.93%). 7.47( ,on knowledge limited exists there, conclusion In. technologies organism-micro indigenous or insemination artificial either their assess later and technologies these on farmers train to need therefore is There. technologies three the of use and .
Keywords: Local Feed formula, organisms-Micro Indigenous, livelihoods, Artificial insemination